The aspects of specialists’ professional ethic qualities enhancement in training - Almaz, Nurazkhan; Toty, Turganbayeva; Bazargul, Kulzhagarova; Vladimir, Eshpanov; Kairat, Smagulov; Assel, Yerbolova (International Journal of Psychosocial Rehabilitation, 2020)
The formation of moral qualities among students of pedagogical institutions is of fundamental importance, because their presence must be successful and consider all professional functions, which necessitates the formation of high-quality qualitative indicators in the future. This article is devoted to the formation of moral qualities of future teachers in the specialty: "Pedagogy and Psychology" with professional training.